Extreme gradient boosting (Xgboost) model to predict the groundwater levels in Selangor Malaysia - Ibrahem Ahmed Osman A.; Najah Ahmed A.; Chow M.F.; Feng Huang Y.; El-Shafie A. (Ain Shams University, 2023)
Forecasting; Groundwater; Learning algorithms; Machine learning; Neural networks; Rain; Support vector regression; Gradient boosting; Machine learning models; Malaysia; Prediction model; Rainfall data; Support vector regression models; Predictive analytics